THE EFFECT OF WORKING ENVIRONMENT ON SPECIALIST PHYSICIANS’ PERFORMANCE AT MEDAN TEACHING HOSPITAL - Silaban, Gerry; Zulfendri; Mardiana Lubis, Arfah; Nasution, Putri (Malaysian Journal of Public Health Medicine, 2021)
The condition of work environment (patient room) is often out of concern to the management so that they do not meet the requirements of Regulation of Minister of Health of the Republic of Indonesia (Permenkes) No. 1204 of 2004 concerning Hospital Environmental Health Requirements. It will have implications for the performance of the doctor (specialist). This study aimed to describe the conditions of the work environment (temperature, lighting, and dust) and the doctor's performance and the relationship between the work environment and the doctor's performance. This research was a quantitative study with a cross sectional design. The research was conducted in 3 teaching hospitals in Medan, namely H. Adam Malik Hospital, dr. Pirngadi and RSU USU during April - November 2018. The study population was 236 people with a sample of 22 people taken using incidental sampling technique. The data obtained by measuring the conditions of the work environment (temperature, lighting, and dust) and interviews using a questionnaire to measure the performance of doctors. Data analysis used Fisher's Exact Test. The results showed that there was no influence of work environment conditions on the doctor's performance, however the temperature and lighting conditions did not meet the requirements. Meanwhile, the temperature of the work room affected the behavior of doctors. Thus, the hospital management needs to take corrective action on working environment conditions by replacing old air conditioners or regularly maintaining air conditioners, setting up a barrier against noise sources, and replacing the bulb with a lighter intensity. The medical committee needs to regularly supervise the work of doctors so that their performance is achieved according to the target.